SUSTAINABLE ANTIMICROBIAL FINISHING OF FABRICS USING NATURAL BIOACTIVE AGENTS - A REVIEW: Life Sciences-Biology - A.RESHMA; V.BRINDHA PRIYADARISINI; K. AMUTHA (International Journal of Life Science and Pharma Research, 2022)
Antimicrobial textiles have gained much attention and popularity in the market and in day- to-day life during the last two decades. The textile industries continue to introduce different methods in their production to enhance the quality of their products and to satisfy their customers. Increased competition in the industry has lead to the development of different synthetic antimicrobial agents. Though these synthetic agents are used widely, they pose a threat to both the users and the environment. Taking into consideration these threatening issues, several environmental bodies have implemented rules in the use of synthetic agents. On the contrary, the natural antimicrobial agents which have less adverse effect on humans and are eco friendly, are gaining much attention. Several natural agents such as basil (active agent is eugenol), neem (active limnoids like azadirachtin, nimbinin), turmeric (curcumin), clove oil, chitosan, sercin, onion, aloevera and pomegranate have antimicrobial properties. This review paper highlights the different natural antimicrobial sources, their effect on public and the possibilities of using these agents in textiles to impart antimicrobial properties and to develop different products.